2000
DOI: 10.1067/mva.2000.109211
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial versus intimal liposome-mediated ex vivo transfection of canine saphenous vein grafts with endothelial nitric oxide synthase gene

Abstract: These results suggest that ecNOS transfection of vein grafts is feasible through intimal and adventitial routes with naked DNA or a liposomal vector. However, efficient transcription of the transgene is evident at postoperative day 3 only after adventitial transfection of 100 microg/mL of the gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
1
14
1
Order By: Relevance
“…Further evidence for a beneficial role of adventitial NO delivery comes from gene transfer studies where it has been shown that adventitia-dependent arterial relaxation occurs following transduction with recombinant eNOS gene [25] and that adventitial transfection of eNOS gene is more effective in reducing graft occlusion than intravascular delivery [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for a beneficial role of adventitial NO delivery comes from gene transfer studies where it has been shown that adventitia-dependent arterial relaxation occurs following transduction with recombinant eNOS gene [25] and that adventitial transfection of eNOS gene is more effective in reducing graft occlusion than intravascular delivery [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription reaction was performed with 5 g of pure total RNA using SuperScript™ II reverse transcriptase (Invitrogen). Synthesized cDNA was amplified by PCR using the following primers: (1) vWF, 15 sense 5Ј-TGG ATG AGC TTT TGC AGA CC-3Ј, antisense 5Ј-GTG GGA GCC GTC GTG GTA CT-3Ј; (2) endothelial nitric oxide synthase (eNOS), 16 sense 5Ј-TCA ACC AGT ACT ACA GCT CC-3Ј, antisense 5Ј-GTG GTT GCA GAT GTA GGT GA-3Ј; (3) kinase-insert domain-containing receptor (KDR), 17 sense 5Ј-TTC CTG ACC TTG GAG CAT CT-3Ј, antisense 5Ј-AGT CCA GCA TGG TCT GGT AC-3Ј; (4) ribosome s17, 15 sense 5Ј-GAA GGC GGC CCG GGT CAT CA-3Ј, antisense 5Ј-GTA GGC TGA GTG ACC TG-3Ј. PCR was carried out for 30 cycles of denaturing (94°C, 30 s), annealing (60°C, 30 s), and extension (72°C, 45 s) with a final extension at 72°C for 7 min.…”
Section: Semiquantitative Analysis Using Rt-pcrmentioning
confidence: 99%
“…All of these vectors, however, exhibit fairly low penetrance into vascular tissue when the basement membrane is intact. [6][7][8][9][10][11][12] Therefore, most strategies have stipulated preemptive mechanical denudation of the endothelium, followed by delivery of very high doses of vector. Even with these modifications, the observed duration of reporter gene expression has been limited, and most of its biological activity is undetectable by the end of the first week.…”
Section: Introductionmentioning
confidence: 99%